(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Cotton fabric is treated with a chicken-feather protein derivative auxiliary (named WLS-10) and with a self-made linking cationic agent (named WLS), respectively. WLS-10 was prepared with chicken-feather protein and WLS. The salt-free reactive dyeing properties of the treated cotton fabric were assessed and compared with the untreated cotton fabric dyed with salt. The results show that both the cotton fabrics treated with WLS-10 and WLS dyed without added salt obtained a higher dye uptake (E), color strength value (K=S), fixation of adsorbed dye (F) and the total fixation of the original applied dye (T) than untreated cotton fabric dyed with added salt. The treated cotton fabric did not decrease levelness and color fastness. However the dyeing properties of the WLS-10 treated cotton fabric were better than the WLS treated fabric.